THE PHENOMENON OF (ISLAMIC) RELIGIOUS FUNDAMENTALISM IN A NON-‘RELIGIOUS’ CAMPUS: A CASE STUDY AT HASANUDDIN UNIVERSITY MAKASSAR - Taufani Taufani (Al-Albab, 2014)
This research aims to describe and examine the phenomenon of Islamic fundamentalism on the campus of Hasanuddin University (UNHAS). Islamic fundamentalism is a phenomenon that emerged after the reform and it is commonly encountered in the campus world. The trend shows that the phenomenon of Islamic fundamentalism is growing in the campus that has no particular religious affiliation and is often driven by the propagation of the Campus Dakwah Organization (LDK). This research would like to test the thesis that whether it is relevant to the context of the Hasanuddin University that in fact is not a religiously-affiliated campus or the contrary. The method of collecting data was done through observation of the activities of the LDK activist at the Hasanuddin University (UNHAS) Campus Dakwah Organization’s Musholla Lovers (LDK-MPM), in-depth interviews, documentation/review of previous research and papers. This research shows that Islamic fundamentalism led by LDK-MPM is growing at the Hasanuddin University. This phenomenon emerged as the implications of the post-reform freedom, so that these opportunities are exploited by activists to channel their euphoria, because at the time of the new order, their propagation had a fairly limited space. Another factor that led to the rise of Islamic fundamentalism and growing at Hasanuddin University is because the students did not have comprehensive Islamic references, so that they had no checklist for critiquing and examining the ideology of Islamic fundamentalism. In addition, the emergence of modernity considered to bring the negative excesses also serves as another factor being the cause of Islamic fundamentalism. Therefore, the ideology of Islamic fundamentalism emerged as an alternative to counteract the negative excesses. Keywords: Islamic Fundamentalism, LDK-MPM, Hasanuddin University.